2008
DOI: 10.1007/bf03191013
|View full text |Cite
|
Sign up to set email alerts
|

Determination and pharmacokinetics of danshensu in rat plasma after oral administration of danshen extract using liquid chromatography/tandem mass spectrometry

Abstract: A liquid chromatography/tandem mass spectrometry (LC/MS/MS) method was developed and validated for the determination and pharmacokinetics of danshensu in rat plasma samples using ferulic acid as internal standard (IS). The plasma samples were treated by liquid-liquid extraction, and the analyses were determined using electrospray negative ionization mass spectrometry in selected reaction monitoring (SRM) mode. The signal intensity of the m/z 196.8 --> 134.8 transition of danshensu was found to relate linearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…It is well known that LC-MS is an effective approach for the PK study of compounds in complex matrix samples. Many studies also developed LC-MS methods for PK evaluation of these six compounds [25][26][27][28][29][30]. However, these methods usually focused on only one or two main marker components separately, no global methodology could be given for a comprehensive PK study of JTT.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that LC-MS is an effective approach for the PK study of compounds in complex matrix samples. Many studies also developed LC-MS methods for PK evaluation of these six compounds [25][26][27][28][29][30]. However, these methods usually focused on only one or two main marker components separately, no global methodology could be given for a comprehensive PK study of JTT.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological studies show that it has a variety of pharmacological effects, such as the dilation coronary arteries, anti‐oxidation, inhibition of platelet adhesion and aggregation, anticoagulant, protective effect on endothelial cell, anti‐artery atherosclerosis, and anti‐inflammatory effects . The metabolism of DSS in rat was studied previously in our laboratory and we showed that DSS is extensively metabolized in rats via conjugative (phase II) pathways . Based on peak area ratios of the metabolites to parent drug, the main metabolite of DSS in rat plasma is 4‐hydroxy‐3‐methoxyphenyllactic acid (HMPLA).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous pharmacokinetic studies have been performed for water‐soluble compounds in Danshen. For example, several methods have been developed for the determination of DSS using high performance liquid chromatography connected to ultraviolet detector (HPLC‐UV), liquid chromatography mass spectrometry (LC‐MS) and liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) . So far, no method for the simultaneous determination of DSS and HMPLA in rat plasma has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Serum CA-125 measurement is now a consolidated method for diagnosing endometriosis, and the serum CA-125 values were found significantly elevated in patients with ovarian and mixed endometriosis lesions ( A liquid chromatography/tandem mass spectrometry (LC/MS/MS) method was developed and validated for the determination and pharmacokinetics of danshensu in rat plasma samples using ferulic acid as internal standard (IS) and the validated LC/MS/MS method was applied to a pharmacokinetic study in which the extracts of SMB (ESMB, containing 40 mg/g danshensu) was administered orally to rats at a single dose of 200 mg/kg in 2% water (Li et al, 2008). A dynamic continuous ultrasound-assisted extraction with high intensity ultrasonic probe (CUAE-HIUP) combined with solid-phase extraction (SPE) for preconcentration and clean-up of the extract prior to high-performance liquid chromatography (HPLC) determination of the main biological active ingredients, sodium Danshensu and four tanshinones (dihydrotanshione I, tanshinone I, cryptotanshinone and tanshinone IIA) from root of SMB has also been developed in a recent study.…”
Section: Discussionmentioning
confidence: 99%